Mia, the way the cupcake crumbles - Simon, Coco; West, Tracey, 1965- (Simon, Coco. Cupcake diaries, 2015)
"Mia is having a terrible day! Everything is going wrong. She woke up late and couldn't make her hair look perfect or brush her teeth, she probably failed a pop quiz, and she broke her glasses! But when her mom's cousin Laura arrives from Puerto Rico, she gives Mia a bracelet with a lucky charm. All of a sudden, Mia's luck changes for the better. Mia's thrilled--she'll never have a bad day again--or will she?"--Back cover.